Analisis Determinan Prestasi Belajar pada Siswa Penerima Program Makanan Bergizi Gratis (MBG) di SMP Kota Payakumbuh - Abdul Haris; Denas Symond; Idral Purnakarya (Jurnal Ners, 2026)
Chronic undernutrition in Indonesian school-aged children, with a 21.6% stunting prevalence (SSGI 2022), impairs cognitive development and academic performance in junior high school (SMP) students. This study aimed to identify determinants of academic achievement among Free Nutritious Meals Program (MBG) recipients in SMP Kota Payakumbuh, including nutritional status (BMI-for-age), attendance, MBG acceptability, and breakfast habits. An explanatory sequential mixed-methods cross-sectional design was applied to 243 eighth-grade students at SMPN 4 and SMPN 6 (February–March 2026), using anthropometry, SQ-FFQ, Comstock observation, questionnaires, and SPSS analysis (univariate, chi-square bivariate, logistic regression). Most students showed good nutritional status (70.4%), high attendance (93.4%), and good achievement (75.7%), but low MBG acceptability (46.1% poor) and suboptimal breakfast habits (61.3% skipping). Bivariate analysis indicated significant associations of nutritional status (p=0.035) and attendance (p=0.001) with achievement, whereas MBG acceptability (p=0.997) and breakfast habits (p=0.718) were not significant. These results underscore MBG's potential to enhance achievement via improved nutrition and school participation, recommending menu diversification and sustained nutrition education. (178 words) Keywords: Free Nutritious Meals Program, academic achievement, nutritional status, junior high school students.